Metodologias de Ensino e seus desdobramentos: percepção de professores em formação inicial em Ciências Biológicas - Paz, Milena Sávio Pastorini (2024)
Despite being found at the heart of teaching practice, Teaching Methodologies are often understood in a trivial way, with this term being used in a confusing and little reflected way, without a clear definition of its meaning and relevance. This work has as its central axis Teaching Methodologies within the scope of Science Teaching and the way in which they are perceived and used by teachers in initial training in Biological Sciences based on the following investigative question: what is revealed when teachers in initial training choose the Teaching Methodology in their class? The research participants were five academics from the Biological Sciences Degree course at a public university in western State of Paraná, who took the Supervised Science Internship discipline in 2022. Through qualitative research, with a phenomenological epistemic basis, we aim to understand the perceptions about this phenomenon (Teaching Methodology). The research corpus consisted of internship reports produced by participants and semi-structured interviews. To analyze the data, we adopted the Discursive Textual Analysis (DTA). Three final categories were constructed, named as: 1) Multifaceted and discontinued perceptions about their own training; 2) Between expectation and reality, an abyss: the desire not materialized in the lesson plan; 3) Significant entanglement: how Teaching Methodology is perceived and adopted in the context of the Supervised Internship in Science. The results of the first category point to a fragmented understanding of their own training and the Internship process. The second category discusses the difficulties and challenges faced in planning conducting classes in line with restricted autonomy in the methodological choice experienced by the participating academics throughout the entire Internship process. We identified a difficulty in conveying what they aim for as teachers and what they employ in their teaching practices, and difficulty in reflecting critically on their own performance. In the third category, there is a nebulous and tangled perception of the term Teaching Methodology, being perceived as a set of techniques or just being restricted to the operational dimension of the class. There is also an incongruity in terms, such as the meaning of Didactics, for instance. We consider the existence of a still immature understanding of teacher training with difficulties in looking more comprehensively at the degree course. Likewise, the Internship shows to be a potentially formative and collective experience, however, the effective reflective process does not occur and little importance is given to planning issues, such as Teaching Methodologie